Strong green-emission phosphor Ca2SiO4:Eu2+ to achieve the color constancy and high luminous efficiency for white LEDs - Van Liem Bui; Hsiao-Yi Lee; Thinh Cong Tran (Institute of Advanced Engineering and Science, 2022)
The study uses the green phosphor of Ca2SiO4:Eu2+ to achieve the color constancy for the dual-film remote phosphor white-LED model at low as well as big CCTs. The utilized green phosphor Ca2SiO4:Eu2+ was prepared using the water-soluble-silicon liquid phase precursor method with the doped Eu2+ ion concentration of 3 mol%. The Ca2SiO4:Eu2+ phosphor emits strong green light with emission intensity focused at 502 nm wavelength, and a wide stimulation band of colors of 225 nm – 450 nm. After applying the Ca2SiO4:Eu2+ green phosphor and modifying its concentration, the modified color and luminous performances can be observed. The better color uniformity and higher luminescence efficiency can be obtained by increasing the percentage of Ca2SiO4:Eu2+ in the phosphor configuration. Meanwhile, the color rendering metrics tend to reduce slightly when the concentration of Ca2SiO4:Eu2+ is over 10% wt.